2009
DOI: 10.1128/jcm.01778-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the New Vitek 2 ANC Card for Identification of Medically Relevant Anaerobic Bacteria

Abstract: Of 261 anaerobic clinical isolates tested with the new Vitek 2 ANC card, 257 (98.5%) were correctly identified at the genus level. Among the 251 strains for which identification at the species level is possible with regard to the ANC database, 217 (86.5%) were correctly identified at the species level. Two strains (0.8%) were not identified, and eight were misidentified (3.1%). Of the 21 strains (8.1%) with low-level discrimination results, 14 were correctly identified at the species level by using the recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…Conventional phenotypic identification of anaerobic bacteria to the species level can be difficult and laborious in the clinical microbiology laboratory. Commercial phenotypic systems like the Rapid ID 32A or Vitek 2 ANC card (bioMérieux, Marcy-l'Etoile, France) are faster but limited by the taxa included in the system database and, in most cases, only reliable to the genus level (6,8,11,12,14). In the last few years, the use of 16S rRNA gene sequencing as an alternative method for species identification has increased, while the time and costs (Ϸ$35 to $40) have been reduced (7,8,14,15).…”
mentioning
confidence: 99%
“…Conventional phenotypic identification of anaerobic bacteria to the species level can be difficult and laborious in the clinical microbiology laboratory. Commercial phenotypic systems like the Rapid ID 32A or Vitek 2 ANC card (bioMérieux, Marcy-l'Etoile, France) are faster but limited by the taxa included in the system database and, in most cases, only reliable to the genus level (6,8,11,12,14). In the last few years, the use of 16S rRNA gene sequencing as an alternative method for species identification has increased, while the time and costs (Ϸ$35 to $40) have been reduced (7,8,14,15).…”
mentioning
confidence: 99%
“…However, species and genera not present in the database had been eliminated from their study isolates (15,17). The lower level of correct identification obtained in our clinical study can be explained by the inclusion of test isolates that are not present in the database but are encountered in clinical material.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast to other validations of the ANC card, Mory et al (15) and Rennie et al (17) previously reported correct specieslevel identifications for 86.5% and 95.1% of isolates, respectively. However, species and genera not present in the database had been eliminated from their study isolates (15,17).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations